Edukasi Partisipatif K3 pada Pabrik Kerupuk di Tasikmalaya untuk Meningkatkan Pengetahuan dan Praktik Keselamatan Kerja - Dhea Julia; Dini Martini; Alwan; Nia Herdiani; Dinar Puji Wardani (Catimore: Jurnal Pengabdian Kepada Masyarakat, 2026)
Occupational Safety and Health (K3) is crucial for preventing workplace accidents, which are primarily caused by human factors such as low discipline and non-compliance with Standard Operating Procedures (SOPs) and Personal Protective Equipment (PPE) usage. To address this, a community service activity using a participatory educational approach was conducted to enhance workers' K3 understanding. The intervention's effectiveness was evaluated through pre-test and post-test instruments. Initially, K3 implementation was minimal, characterized by the infrequent use of PPE. However, following the counseling, participants' knowledge increased significantly, evidenced by a statistical p-value of 0.000 (p < 0.05). This proves that the educational intervention effectively improved K3 comprehension. Ultimately, this enhanced knowledge is projected to ensure worker safety, maintain product quality, and boost consumer confidence, thereby driving the market expansion of food MSMEs. Keywords: job safety, education, knowledge.